2018
DOI: 10.1101/314237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global connectivity and function of descending spinal input revealed by 3D microscopy and retrograde transduction

Abstract: The brain communicates with the spinal cord through numerous axon tracts that arise from discrete nuclei, transmit distinct functions, and often collateralize to facilitate the coordination of descending commands. In efforts to restore supraspinal connectivity after injury or disease, this complexity presents a major challenge to interpreting functional outcomes, while the wide distribution of supraspinal nuclei complicates the delivery of therapeutics. Here we harness retrograde viral vectors to overcome thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 40 publications
9
40
0
Order By: Relevance
“…This result is in contrast to the suggestion that for cortically-dependent movements motor commands are conveyed primarily via PT neurons 5,16 . However, our observations are consistent with key roles for subcortical structures such as basal ganglia in the regulation of movement vigor 39,59 , critical functions for extrapyramidal motor pathways in regulating movement execution 60 , and the notion that corticospinal projections are primarily recruited for fine control of dexterity 2,61 rather than gross movement 59 . Our data together with previous work provide evidence that the relative recruitment of IT and PT neuron types is task specific and reflects a flexible routing of motor cortical output through downstream effectors 17 .…”
Section: Discussionsupporting
confidence: 84%
“…This result is in contrast to the suggestion that for cortically-dependent movements motor commands are conveyed primarily via PT neurons 5,16 . However, our observations are consistent with key roles for subcortical structures such as basal ganglia in the regulation of movement vigor 39,59 , critical functions for extrapyramidal motor pathways in regulating movement execution 60 , and the notion that corticospinal projections are primarily recruited for fine control of dexterity 2,61 rather than gross movement 59 . Our data together with previous work provide evidence that the relative recruitment of IT and PT neuron types is task specific and reflects a flexible routing of motor cortical output through downstream effectors 17 .…”
Section: Discussionsupporting
confidence: 84%
“…When analysing the output of S1-CST neurons, we found evidence that, although they mainly project through the CST onto the spinal dorsal horn, they also send collateral branches to the dorsal striatum and the midbrain. This confirms and further specifies previous experiments in which CST collaterals were observed when all spinally projecting neurons were labelled Wang Z et al 2018). Our data therefore indicate that while their main target is the spinal dorsal horn, S1-CST neurons also contribute to cortico-striatal projections and may thereby influence goal-directed behaviours .…”
Section: S1-cst Neurons In Somatosensory Circuitssupporting
confidence: 92%
“…To this end, it would be crucial to restrict transgene expression to the layer 5 pyramidal neurons in an area of the cortex (S1 in this case) that projects to the spinal region of interest such as the dorsal horn of the spinal cord. Recently, a new recombinant adeno-associated virus (rAAV) serotype (rAAV2-retro) (Tervo DG et al 2016) has been developed with greatly improved retrograde labelling efficiency that allows high fidelity tracing of descending inputs to the spinal cord (Haenraets K et al 2017;Wang Z et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a key finding was that delivery of KLF6 by retrograde vectors, but not direct cranial injection, improved forelimb function after spinal injury. We recently characterized retrograde transduction after spinal injections of AAV2-Retro, and showed widespread transduction of CST neurons throughout the cortex, in addition to subcortical nuclei that participate in skilled movements, including the red nucleus and reticular formation (29). The likely explanation for the difference in behavioral outcomes is that compared to focal delivery to subregions of motor cortex, retrograde vectors deliver therapeutic transgenes to a larger number and greater diversity of supraspinal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…To deliver KLF6 more broadly we employed Retro-AAV, a newly developed vector with enhanced retrograde properties. We recently showed that delivery of Retro-AAV to the cervical spinal cord produces highly efficient transduction of CST neurons throughout the cortex, in addition to subcortical populations including the rubrospinal tract (29). To confirm the ability of Retro-AAV to drive KLF6 expression we co-injected Retro-AAV2-KLF6 and Retro-AAV2-tdTomato to cervical spinal cord.…”
Section: Retrograde Klf6 Delivery and Npc Grafting Promote Forelimb Fmentioning
confidence: 99%